The power of literacy: special education students’ perceptions of themselves as literate beings - McNemar, Stephanie K. (Kansas State University, 2015)
This phenomenological case study focuses on three secondary special education students’ perceptions of themselves and their lived experiences. The purpose of this study is twofold: First, to understand how secondary special education students perceive themselves as literate beings; and second, to illuminate how secondary special education students understand what it means to be literate and how their lived experiences have shaped their perceptions of being literate. Based on qualitative data, such as, interviews, observations, questionnaire, and a qualitive analysis method, called Interpretive Phenomenological Analysis, I have identified three themes of the lived experiences of the participants: 1) Students’ stability and/or instability of their lived experiences influenced their literacy practices; 2) Being identified as special education students did not prevent them from being literate; and 3) Different lived experiences led to different literacy practices. Based on these themes, I provide implications for educators and policy makers including: understanding secondary special education (SSE) students as literate beings; valuing the varied experiences that SSE students bring to classrooms; capitalizing on SSE students’ self-efficacy and resilience to promote students’ literacy; respecting SSE students’ literacy skills on out-of-school literacy; paying attention to the personal dimensions of literacy practices to meet the needs of the diverse learners; allowing SSE students to demonstrate their literacies in multiple ways; and collaborating between general education and special education teachers to benefit all students. The significance of this study resides in that it focuses on the literacy practices of secondary special education students, whose voices have been largely missing in the literature. This understanding of the voice and the lived experiences that secondary special education students bring to the classroom will help educators, policy makers, and curriculum writers find ways to better serve special education students. In so doing, this study reconceptualizes the power of literacy that needs to be fostered in SSE students, so that they can succeed not only in college and career but also in their personal lives.
Keywords: phenomenology; adolescent literacy; special education; Reading Instruction (0535); Special Education (0529)